Pretreatment with Misoprostol Reduces Intrauterine Adhesions After Surgical Termination of Missed Abortion - Akgöl, Sedat; Budak, Mehmet Şükrü; Önen, Şahin; Erdem, Selami; Kahyaoğlu, Serkan; Kanat Pektaş, Mine (Gynecology Obstetrics & Reproductive Medicine, 2012)
OBJECTIVE: The present study aims to utilize hysteroscopy in order to determine whether pretreatment with misoprostol reduces intrauterine adhesions after a missed abortion is terminated surgically. STUDY DESIGN: This study reviews 100 women who were diagnosed with missed abortion between 6 and 10 weeks of gestation and who were to be treated with curettage. RESULTS: The visual analogue scale score was significantly lower and the convenience of curettage was significantly better for women who were treated with misoprostol before curettage (respectively, p=0.035 and p=0.001). Acquired intrauterine adhesions were significantly less and the convenience of hysteroscopy was significantly better for women who received pretreatment with misoprostol (respectively, p=0.046 and p=0.001). CONCLUSION: Misoprostol reduces intrauterine adhesions after surgical termination of missed abortion, possibly by improving the convenience of curettage. Pretreatment with misoprostol can be justified for women who have history of infertility or recurrent pregnancy loss and who are to undergo curettage.